DEVELOPMENT OF LEARNING DEVICES AND ITS IMPLEMENTATION THROUGH THE STAD TYPE OF COOPERATIVE LEARNING MODEL IN INCREASING LEARNING MOTIVATION ELEMENTARY SCHOOL STUDENTS - Abdul Wahid; Ashar Ashar; Syarifah Aeni Rahman; Indri Mudiarti; Vina Sundari; Sitti Fadhillah Ilham; Al Aswar (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This study aims to determine the increase in motivation, student learning with the development of learning tools and their implementation through the 2013 curriculum and the independent curriculum with the application of the STAD Type Cooperative Learning model. critical of a learning plan by the teacher, teacher interaction with students, and how students interact in class Improvement of the implementation of the learning process in class from cycle I with an average score of 31.57% with the category not achieving the predetermined success criteria and in cycle II with a value reaching 52.63% This means that the research indicators have been achieved and there is no need to continue in the next cycle